4th industrial revolution turned hurdles for the capital market in Bangladesh: Possibilities and problems - Tasfia, Naziza (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.